DEFENSIVE BATTLES OF THE UPR ARMY IN THE PODILLIA IN THE SUMMER OF 1920 - OLIINYK , Serhiy; STEFANYSHYN, Olena (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2025)
The article highlights the defensive battles of the UPR army in Podillia in July 1920 based on the use of various sources and scientific literature. This page of national history is an important component of the study of the events leading up to the Ukrainian Revolution of 1917-1921 and has great importance for creating an objective and holistic picture of it. The research methodology is based on the principles of historicism and objectivity. The use of methods such as analysis, synthesis, as well as problematic and chronological, systematic, descriptive, statistical and comparative, made it possible to achieve the goal. The above-mentioned events did not receive proper coverage in historiography, and were sometimes subjected to falsification and distortion, which, of course, is an important motivating factor for their development. Scientific works of national historians have done a lot in this regard. However, the existing scientific heritage does not allow for a holistic disclosure and presentation of the events related to the defensive battles of the UPR army in Podillia in the summer of 1920. Important attention is paid to clarifying the military and political conditions in which the UPR army found itself during this period, and the factors that contributed or did not contribute to the effective confrontation of Ukrainian units with the Red Army forces are revealed. An attempt is made to determine the composition of the warring parties, their numbers, weapons, etc. The author traces in chronological sequence the combat path of the UPR army in Podillia during the summer of 1920: 1) 1-12 June, when units of the UPR army were involved in the initial phase of confrontation with the Soviet offensive that began on 26 May; 2) 13 June-13 July, defensive battles during the retreat to the Zbruch River; 3) 14-26 July, defense along the Zbruch River. There is an attempt to analyse in detail the entire range of defensive and counter-offensive actions carried out by the Ukrainian army. In addition, their specificity is determined in accordance with the three stages of the summer defensive battles that took place in Podillia in 1920. The results and consequences of the combat operations are also noted. The attempt is made to analyse them not only at the tactical but also at the strategic level. Special attention is drawn to examples of military skill, courage and heroism displayed by soldiers and commanders of the UPR army during defensive battles in Podillia in the summer of 1920